A bioinformatic analysis of the Duchenne muscular dystrophy gene and associated gene variants across human cancers - Machado, Lee (2022)
The Duchenne muscular dystrophy (DMD) gene and its major translated protein product Dystrophin (Dp427m) have for decades been associated with musculoskeletal function, with specific mutations giving rise to dysfunction in Duchenne and Becker muscular dystrophies. Alterations in the expression of the DMD gene have recently been associated with the development, progression, and survival outcomes of several tumours.